Government and Governance Reforms in Africa - Varghese, N.V. (International Higher Education, 2013)
Several African countries have implemented reforms in higher education governance in recent years. Many of these reforms were because of expansion and declining quality. Efforts have been made to reduce dependence on the state and increase market forces into the higher education equation.